Environmental compliance: a place in the legal environmental system - Makarova, Tamara I.; Kvanina, Valentina V. (Journal of the Belarusian State University. Law, 2020)
The article presents the results of a study of the concept «environmental compliance» as an innovative direction of legal science and law of the Republic of Belarus and the Russian Federation. The basis of this research is the theory of legal mechanisms for environmental protection and the environmental measures, which are institutions of environmental law. It is concluded that the content of environmental compliance is similar to the function of environmental control, which allows us to determine the legal forms of environmental compliance, and environmental and legal requirements are its legal basis. It is proved that environmental compliance should be considered as an applied tool which is a program that includes the optimal set of environmental measures necessary to implement the environmental policy of a particular business entity.